Healthcare Knowledge Management Primer - Wickramasinghe, N. S.; Bali, Rajeev K.; Lehaney, Brian; Schaffer, Jonathan; Gibbons, M. Chris; Abd Ghani, Mohd Khanapi (Routledge, 2009)
Quality care of patients requires evaluating large amounts of data at the right time and place and in the correct context. With the advent of electronic health records, data warehouses now provide information at the point of care and facilitate a continuous learning environment in which lessons learned can provide updates to clinical, administrative, and financial processes. Given the advancement of the information tools and techniques of today’s knowledge economy, utilizing these resources are imperative for effective healthcare. Thus, the principles of Knowledge Management (KM) are now essential for quality healthcare management.